Microbial Culture Characteristics and Antimicrobial Susceptibility Patterns Associated with Vesicovaginal Fistula - Gugum Indra Firdaus; Tjahjodjati Tjahjodjati (Majalah Kedokteran Bandung, 2022)
Vesicovaginal fistula (VVF) is commonly linked with recurrent urinary tract infection (UTI). Thus, the patterns of the pathogenic microorganism becomes important consideration in the management of this disease. This study aimed to describe patient profiles, disease etiology, and antimicrobial susceptibility patterns of microorganisms in VVF patients. This retrospective study was conducted on 49 medical records of vesicovaginal fistula patients seen from January 2016 to December 2020. The most prevalent age group of the patients was 40-50 years old. Analysis demonstrated that the leading etiology for VVF among these patients was malignancy (73.47%). The antimicrobial susceptibility was tested using the disc diffusion method and Escherichia coli (44.90%) and Proteus mirabilis (14.29%) were identified as the bacterial pathogens most frequently isolated from urine samples. Of the 39 patients with significant growth of organism cases, 29 (74.35%) had symptomatic UTIs. The isolated gram-negative bacteria had excellent sensitivity to aztreonam, ertapenem, and meropenem, with a more than 90% susceptibility rate, while the  gram-positive bacteria had good sensitivity to amikacin, cefepime, tigecycline, aztreonam, ertapenem, and meropenem, with a more than 90% susceptibility. In conclusion,  bacterial culture and antibiotic susceptibility test (AST) remains an essential part of managing VVF and their results can be used as a reference for empirical therapy. Amikacin, cefepime, tigecycline, aztreonam, ertapenem, and meropenem should be considered for treatment of UTIs associated with VVF.